Pengaruh Pemanfaatan E-Learning dan Minat Belajar Terhadap Perilaku Belajar Mahasiswa Fakultas Ekonomi Stambuk 2017 Universitas Negeri Medan - Desi Purnama Dewi; Alfi Nura (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2021)
The problems in this research are students difficulties in using e-learning, students interest in learning is still low and student learning behavior is not good. The purpose of this study was to determine how the influence of the use of e-learning and interest in learning on the learning behavior of students of the Faculty of Economics, Stambuk 2017, State University of Medan. This research was conducted at the Faculty of Economics, Medan State University, which is located on Jl. Willem Iskandar Pasar V Medan. This type of research is ex post facto. The population of this study was 629 students with a sample of 86 students using simple random sampling technique. The data collection technique used is a questionnaire. Before being used, the questionnaire was tested for validity and reliability. Then the data was collected and the results of the questionnaire were analyzed using multiple regression. From the results of the partial test analysis between the use of e-learning (X1) on learning behavior (Y) from the value of  >  (4.274 > 1.663) with a significance value smaller than the 0.05 level (0.000 < 0.05) and for the significance value between learning interest (X2) and learning behavior (Y) from the value of  >  (8,575 > 1,663) with a significance value less than 0.05 level (0.000 < 0.05). Simultaneously (F test) the value is shown that  >  (121.105 > 3.11) and a significant value of 0.000 <0.05. Thus, it can be concluded that the influence of the use of e-learning and interest in learning has a positive and significant influence on the learning behavior of students of the 2017 Stambuk Economics Faculty, State University of Medan